Self-Healing Hydrogels Based on Chitosan and Banana Sap for Sustainable Wound Dressing Applications - Stenly Komansilan; Tiara Nisa Fauziah (CV. Get Press Indonesia, 2026)
Wound dressings with self-healing properties represent a significant advancement in modern wound management. This study reports the development of self-healing hydrogels fabricated from chitosan and Musa acuminata (Cavendish banana) stem sap, reinforced with genipin as a natural crosslinker a green chemistry alternative to cytotoxic synthetic crosslinkers. Five formulations (F1–F5) were prepared by varying chitosan (1.0–2.0% w/v) and banana sap (5–20% v/v) concentrations. The optimized formulation (F5) achieved a self-healing time of 22 ± 1.2 minutes, swelling ratio of 423 ± 12.0%, tensile strength of 36.8 ± 2.3 kPa, and water vapor transmission rate (WVTR) of 968 ± 19 g/m²/day. FTIR spectroscopy confirmed dynamic Schiff base bond formation responsible for self-healing, and SEM revealed a porous three-dimensional network conducive to moisture retention. F5 demonstrated broad-spectrum antibacterial activity against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa (zones of inhibition up to 19.2 mm), and confirmed biocompatibility with L929 fibroblast cell viability exceeding 91%. In vivo studies in Sprague-Dawley rats demonstrated 94.8% wound closure by day 14, compared to 81.2% for untreated controls. These results establish chitosan banana sap hydrogels as promising, sustainable biomaterials for next-generation wound dressing applications.